ANALISIS YURIDIS TENTANG HAK GUNA BANGUNAN DI ATAS HAK PENGELOLAAN YANG TELAH BERAKHIR MASA WAKTUNYA DAN DIGANTI MENJADI HAK SEWA SELAMA 5 TAHUN - Kelvin Kelvin (LLPM Universitas Deli Sumatera, 2021)
Building Use Rights on State Land and Management Rights Lands are granted for a maximum period of 30 years, and for the right holder, taking into account the needs and conditions of the buildings, this period can be extended for a maximum period of 20 years and renew.for a maximum period of 30 years. The right of building management on land rights can be extended or renew to the holder of the right to use the building if it meets the requirements and gets approval from the owner of the right of management. Keywords: Building Use Rights; Management Rights; Rental Rights